THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND INTERPERSONAL COMMUNICATION ON THE WORK EFFECTIVENESS OF LEADING TEACHERS: AN EMPIRICAL STUDY IN ELEMENTARY SCHOOLS, BOGOR REGENCY - Yusef Gunawan; Sri Setyaningsih; Griet Helena Laihad; Hailu Elias (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
This study aimed to examine the direct effect of transformational leadership and interpersonal communication on the work effectiveness of leading teachers in elementary schools in Bogor Regency, within the context of implementing the Kurikulum Merdeka (Independent Curriculum). The population consisted of 435 leading teachers, with a sample of 116 teachers selected using multistage random sampling (George, 2021). A quantitative, survey-based approach was employed, and data were analyzed using path analysis. The results indicated that transformational leadership had a positive and significant effect on work effectiveness (β = 0.602; p < 0.05), as did interpersonal communication (β = 0.146; p < 0.05). Together, both variables explained 66.2% of the variance in work effectiveness. These findings confirm that strengthening principals' transformational leadership and improving the quality of interpersonal communication are key strategies for enhancing the work effectiveness of leading teachers. Practical implications are discussed.